2018
DOI: 10.3389/fpsyg.2018.00074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Eye Movement Desensitization Reprocessing and Cognitive Behavioral Therapy as Adjunctive Treatments for Recurrent Depression: The European Depression EMDR Network (EDEN) Randomized Controlled Trial

Abstract: Background: Treatment of recurrent depressive disorders is currently only moderately successful. Increasing evidence suggests a significant relationship between adverse childhood experiences and recurrent depressive disorders, suggesting that trauma-based interventions could be useful for these patients.Objectives: To investigate the efficacy of Eye Movement Desensitization and Reprocessing therapy (EMDR) in addition to antidepressant medication (ADM) in treating recurrent depression.Design: A non-inferiority,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 57 publications
(63 reference statements)
3
39
0
2
Order By: Relevance
“…Furthermore, in the present study, only EMDR was found to be effective in reducing depressive symptoms, as previously demonstrated in other patient groups (Carletto et al, 2017;Chen et al, 2014;Ostacoli et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in the present study, only EMDR was found to be effective in reducing depressive symptoms, as previously demonstrated in other patient groups (Carletto et al, 2017;Chen et al, 2014;Ostacoli et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…In the past 5 years, several studies have been conducted demonstrating preliminary evidence for the efficacy of EMDR therapy in the treatment of MDD in adults. Promising results were obtained from studies investigating EMDR therapy as an adjacent therapy to CBT (Hofmann et al, 2014), to pharmacological treatment (Minelli et al, 2019;Ostacoli et al, 2018) and to inpatient treatment (Hase et al, 2015(Hase et al, , 2018. Three studies, investigating the efficacy of EMDR as a stand-alone treatment, demonstrated significant reductions of depressive symptoms (Gauhar, 2016), even for patients with long-term depression (Wood, Ricketts, & Parry, 2018) and treatment-resistant depression (Minelli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Much as EMDR is a proven psychotherapeutic approach in posttraumatic stress disorder, there are studies about efficiency in some other psychiatric disorders (Banerjee & Argaez 2017). In addition it can be conducted on various cases in addition to other treatments such as medication or another therapy (Ostacoli et al 2018).…”
Section: Introductionmentioning
confidence: 99%